(untitled) (Archives of Criminology, 2004)
This report devoted to presenting the probation system in Poland together with the duties performed by probation officers is made up of two chapters. In the first chapter all primary legal acts regulating the institutions of the probation officers were discussed, also with the functions they perform in the system of criminal justice. In the second chapter, results of research conducted in all court districts in Poland in 2002 were presented. Both, the analysis of legal regulations, as well as the research, have been conducted after the implementation of the basic reform in Poland, yet there is still a lot to be done organisation wise, i.e. enlarging the number of probation officers, improving their essential preparation as well as implementing modem and effective forms of activity. In the first chapter, where the legal bases of probation officers are discussed, the most important legal acts were mentioned first. Their number is quite substantial, since in the nine laws there are regulations concerning the socio-legal status and duties of probation officers. In order to indicate the most significant of them the following cannot be omitted: The Penal Code of 1997 which regulated matters concerned with probation officers performing a number of supervisory forms (including probation); The Executive Penal Code of 1997 by means of which piobation officers were given a rank of one of the important organs responsible for executing punishments and means of punishment. These tasks have been extended in order to grant the probation officers: executing the punishment of restriction of liberty and substitutive penalty ‒ community service, and also certain duties have been precised concerned with executing the punishment of deprivation of liberty and providing the post penitentiary help. The law on the organisation of law courts (dated from 2001) in which only few articles are devoted to probation. They are, however, immensely important because they helped to precise this system, constituting that probation officers are an autonomous organ operating within the judiciary system, meaning by that regional and district courts, towards which presidents of the law courts and judges occupy supervisory and controlling positions. Simultaneously, the professional and social character of the probation officer has been confirmed in that law. Another very important legal act is the law of 1982 on the procedures in juvenile cases (with later changes, especially with a very thorough amendment of 2000) which regulates the use of probation (family courts) in cases of defining the supervisory methods or reformative for the juveniles. Amongst the discussed laws one, from 2001, about the probation officers is of a special significance. This law has almost a pioneer character. It has been created by the Polish Parliament from the initiative of probation officers and with their considerable participation. While enacted from the beginning of 2002, it has normalised in a complex way the socio-professional status of probation officers and precisely settled the location, organisation and the duties ofthe probation service in the judiciary system. In this report laws and obligations of probation officers have been discussed, together with their calling and prospects for promotion, as well as competence connected with performing duties foreseen in the law of probation officers, and other laws, especially in the Penal Code, the Executive Penal Code, Code of Penal Procedure and in the Civil Code. The bills conceming the probation service and the persons of probation officers, are an additional documentation to the executive acts, to the regulations and orders of the court. In example we can mention one of the most significant regulations, created by the Minister of Justice in 2003, in matter of a detailed executing of the authorities and obligations of probation officers. In the second chapter the activity of probation officers in 2002 has been presented, in the light of the research results. They were conducted by sending a questionnaire to all 40 court regions (all together 150 questionnaires, part of which has been filled in in groups). It needs to be stressed at this point that amongst the questions none of the issues which could be called stressful were taken up. The research included 50 different issues, amongst which the following should be discussed: - kinds and number of performed interviews by the probation officers during the time of criminal proceedings and later of executing, - executing of measures to examine a convicted offender in case of conditional discontinuance of legal penal proceedings, a conditional suspension of penalty execution, a conditional release from serving the full sentence, - the content of adjudged and executed guardianship, in other words what is the character of probation officers’ contacts and work with persons under their ward, - ęxecuting of penalty of imprisonment and community service, - activity in the area of executing the penalty of imprisonment, - the difficulties in the work of probation officers, - opinions of probation officers concerned with cooperation with social workers as well as in reference to the significance of specific purposes of penalty. It is difficurt to summarise the research results. Therefore, only for the purpose of a small illustration, the following conclusions can be mentioned: - probation officers’ opinion about their insufficient number (there is about 2000 professional probation officers for adults) in order to be effective in the assigned roles, - the legal system seems to have achieved a desired state, - supervisions performed by probation officers do not comply with all the obligatory (i.e.- caring - job finding); however, the controlling functions over the sentenced under supervision seem to be accepted as satisfactory.